Step regulation in Paralympic long jumpers with intellectual impairment - Adrián García-Fresneda; Apostolos S. Theodorou; Vassilios Panoutsakopoulos; Miguel Angel Torralba Jordán; Josep-Maria Padullés; Xavier Padullés; Mariana C. Kotzamanidou (European Federation of Adapted Physical Activity, 2022)
Long jump has been extensively used in the investigation of perception-action coupling. The restraints imposed by the tasks nested at the take-off board compel skilled long jumpers to adjust the length of the final 4-5 steps of the run-up based on visual input informing about time-to-arrival. This exploratory study examined the visual regulation parameters in athletes with intellectual impairment (II) during the approach of the long jump. The approach run of 10 elite level T20  Class long jumpers (IIJ) and 10 international level long jumpers without II (NIJ) was recorded during competition. An initial ascending variability of foot placement was observed for both groups, followed by a descending one in the late phase of the approach. The parameters associated with the onset of visual control for IIJ were found to be not statistically significantly different to those of NIJ. The mean maximum toe-board distance variability was 0.38 m and 0.27 m for IIJ and NIJ, respectively. The onset of regulation commenced at the fifth- and third-to-last step for IIJ and NIJ, respectively. The finding that IIJ adjust the last steps of the run-up with sufficient accuracy suggests the presence of visual control. This information can be used to optimize long jump approach run training for athletes with II.